Multi-product Exporters: Product Churning, Uncertainty and Export Discoveries - Iacovone, Leonardo (2012)
Recent research on international trade focuses on firm-product-level heterogeneity and the role of uncertainty in shaping international trade. This article contributes to the literature by examining product-level dynamics within firms in the context of Mexican trade integration under NAFTA. The data show intense product churning within firms and confirm the existence of within-firm product heterogeneity. The data indicate that new exporters enter foreign markets with a small number of varieties, most of which were previously sold at home, and with a small export small volume. The data also suggest that export discoveries are relatively rare and are imitated within a short period of time.